Perception of English Stress of Synthesized Words by Three Chinese Dialect Groups - Guo, Xingrong; Chen, Xiaoxiang (Frontiers in Psychology, 2022)
This study investigated the possible prosodic transfer influences native regional dialects may have in the perception of English lexical stress by speakers of three Chinese dialects (Beijing, Changsha, Guangzhou) compared to 20 American English speakers. F0, duration, intensity, and vowel reduction were manipulated in nonce disyllabic words. Participants performed four-word sequence-recall tasks to identify lexical stress location. They performed better with natural sounds than with manipulated words. This study focused on the performance differences in manipulating words. Results showed that all four-group members performed similarly processing F0 condition nonce words. Beijing and Changsha participants were more accurate than Guangzhou participants in duration and vowel reduction cues. Reaction time suggested that processing time of acoustic cues differed significantly across language groups. Findings indicate that L1 dialect effect is robust in the L2 stress perception tasks.